Optimization of Alternative CMC Sources from Rice Husk, Sawdust, and Caustic Soda, and The Effect of PH Increase on Filtration Loss and Rheology of Drilling Mud - Samura, Lisa; Rosyidan , Cahaya; Maulani , Mustamina; Prima, Andry; Djumantara, Maman; Chusniyah , Dina Asmaul; Fattahanisa , Aqlyna; Satiyawira, Bayu; Mentari Gracia Soekardy; Brilliani (Scientific Contributions Oil and Gas, 2025)
Drilling mud plays a vital role in maintaining wellbore stability, carrying cuttings, and controlling formation pressure during drilling operations. Typically, Carboxy Methyl Cellulose (CMC) is used to enhance mud viscosity and reduce filtration loss, but its synthetic nature makes it relatively expensive. This study investigates rice husk and sawdust as natural, cost-effective alternatives to CMC. Various compositions were evaluated using the Box-Behnken design in Response Surface Methodology (RSM) to optimize the mud formulation. Results indicate that a combination of 6 g rice husk and 6 g sawdust provides the best performance in improving rheological properties such as yield point and gel strength, while significantly reducing filtration loss. Gradual addition of caustic soda (NaOH) effectively increases mud pH to the ideal range (9–11), enhancing chemical stability. RSM successfully modeled the statistical relationship among variables and facilitated identification of the optimal formulation.